2019
DOI: 10.1016/j.bbmt.2018.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Reduced-Intensity Conditioning Allogeneic Hematopoietic Cell Transplantation Performed in the Inpatient versus Outpatient Setting

Abstract: A B S T R A C T Allogeneic hematopoietic cell transplantation (allo-HCT) with reduced-intensity conditioning (RIC) is commonly performed as an inpatient procedure. The feasibility and outcomes of RIC allo-HCT in the outpatient setting is not known. We performed a single-center retrospective cohort study of patients aged 18 years with hematologic malignancies who underwent RIC allo-HCT either in the inpatient or outpatient setting. Donor types included HLA-matched sibling and well-matched unrelated donors. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Outpatient HCT is not a novel idea but until recently has predominantly been reserved for autologous stem cell transplant, particularly in myeloma patients [7,8]. Several centers have published their data regarding outpatient allogeneic HCT using RIC/NMA and myeloablative conditioning regimens and have demonstrated safety and feasibility [3,9,10]. The present data from Fred Hutchinson Cancer Center corroborates that.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Outpatient HCT is not a novel idea but until recently has predominantly been reserved for autologous stem cell transplant, particularly in myeloma patients [7,8]. Several centers have published their data regarding outpatient allogeneic HCT using RIC/NMA and myeloablative conditioning regimens and have demonstrated safety and feasibility [3,9,10]. The present data from Fred Hutchinson Cancer Center corroborates that.…”
supporting
confidence: 77%
“…The outpatient approach to transplant should decrease hospital admissionÀrelated expenses. Guru Murthy et al [9] demonstrated cost savings within the first 100 days of transplant when comparing outpatient RIC allogeneic HCT with their inpatient cohort (median total charges, $247,334 versus $339,621, respectively). Although overall expenses are decreased by outpatient transplant, specific cost savings for institutions and patients may be more difficult to demonstrate.…”
mentioning
confidence: 99%
“…HSCT in outpatient settings has demonstrated to be safe and efficient 13,33 . It also showed no inferiority in survival and lower costs when compared with inpatient protocols 14 . However, there is a lack of information focused on second HSCT in outpatient settings and results in this report provide evidence of a good risk‐benefit balance.…”
Section: Discussionmentioning
confidence: 70%
“…The relatively low toxicity of RIC makes outpatient HSCT possible without increasing the morbimortality 13 . Furthermore, the costs of hematopoietic transplants are considerably reduced when performed in an outpatient setting, 14 which is very important in low‐middle income countries, as recently summarized 15 . Data about the efficacy and cost structure of the outpatient transplantation program in our center have been previously reported 16,17 ; however, information regarding outpatient second HSCT using RIC is scarce, with only one study available in the literature 18 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent single-center retrospective study compared complications and survivals among 116 inpatients and 35 outpatients treated with reduced-intensity conditioning (RIC) conditioning before allogeneic HCT [23]. Short-term outcomes were comparable among both cohorts, with inpatients experiencing 1-year NRM of 10.8% compared with 3.2% among outpatients.…”
Section: Discussionmentioning
confidence: 99%